Intravesical Injection of Botulinum Toxin Type A in Men without Bladder Outlet Obstruction and Post-Deobstructive Prostate Surgery - Lee, Hsiang-Ying; Kuo, Hann-Chorng (Toxins, 2023)
Purpose: A significant proportion of men without bladder outlet obstruction (BOO) have been reported to have overactive bladders (OAB). This article aimed to review the specific group of reports on the use of botulinum toxin type A (BTX-A) injections into the bladder wall. Materials and methods: Original articles reporting men with small prostates without BOO were identified through a literature search using the PubMed and EMBASE databases. Finally, we included 18 articles that reviewed the efficacy and adverse effects of BTX-A injections in men. Results: Of the 18 articles screened, 13 demonstrated the therapeutic efficacy and adverse effects of BTX-A injections in men. Three studies compared BTX-A injection response between patients without prior prostate surgery and those undergoing prior prostate surgery, including transurethral resection of the prostate and radical prostatectomy (RP). Patients with prior RP experienced better efficacy and had a low risk of side effects. Two studies focused on patients who had undergone prior surgery for stress urinary incontinence, including male sling and artificial urethral sphincter surgery. The BTX-A injection was a safe and effective procedure for this specific group. OAB in men was found to have a different pathophysiology mechanism from that in female patients, which may decrease the efficacy of BTX-A injection in men. However, patients with small prostates and low prostate-specific antigen levels demonstrated better efficacy and tolerability after BTX-A injection. Conclusions: Although intravesical injection of BTX-A was a good option for controlling refractory OAB in men, the evidence-based guidelines are still limited. Further research is necessary to better understand the role of BTX-A injections on various aspects and histories. Therefore, treating patients using strategies tailored to their individual conditions is important.